A case of recurrent chronic eosinophilic pneumonia after switching from benralizumab to dupilumab - Daiki Nakashima; Eri Mori; Nobuyoshi Otori (Respiratory Medicine Case Reports, 2024)
Dupilumab inhibits interleukin-4Rα and suppresses type 2 inflammation. Careful administration of dupilumab is required because it increases the blood eosinophil count secondary to a decrease in local eosinophil counts, sometimes resulting in eosinophilic complications. We herein report a case of recurrent chronic eosinophilic pneumonia after switching from benralizumab to dupilumab. A 54-year-old man with a history of eosinophilic pneumonia presented to our hospital with symptoms of cough, fever, and phlegm production six months after beginning dupilumab administration for recurrent chronic rhinosinusitis. When using dupilumab, it is essential to carefully monitor patients’ eosinophil trends and pulmonary symptoms.